Pemanfataan Lahan Pekarangan Guna Menghasilkan Sayur Organik di Desa Sumbersalak Kecamatan Ledokombo Jember - Purwandhini, Ari Septianingtyas; Arini, Silvia Fitri Mei; Syarief, Mochamad; Hadi, Abdul; Qurtubi, Moh. (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
The service activity entitled Socialization of the Use of Yard Land to Produce Organic Vegetables in Sumbersalak Village, Ledokombo District, Jember, is a form of socialization and education for the community to increase the useful value of yard land. The aim of the activity is to maximize the role of yard land in cultivating plants, especially to produce healthy (organic) vegetables. The method used uses lecture and discussion methods. The results of the activity are community understanding of the importance of managing yard land so that it can become a source of nutritional fulfillment for families in an effort to create healthy vegetables free of chemical pesticides. So that similar activities can continue to be developed and utilized by the community to minimize the use of chemical pesticides in plant cultivation activities. Managing organic vegetables can also increase family income.